Stormy Persuasion - Lindsey, Johanna; Copyright Paperback Collection (Library of Congress) (New York, NY : Pocket Books, a division of Simon & Schuster, Inc., 2015)
Postponing her London debut to join her cousin and best friend in America, Judith Malory meets deckhand Nathan Tremayne, an undercover smuggler who is escaping a death sentence.
Keywords: Malory family (Fictional characters) -- Fiction; Aristocracy (Social class) -- Fiction -- England; Man-woman relationships -- Fiction; Smugglers -- Fiction; Love stories; Historical fiction; Regency fiction